Septumplastik: ein Update - Baumann, Ingo (Laryngo-Rhino-Otologie, 2010)
Septoplasty is one of the most frequently performed otorhinolaryngological procedures which might be very challenging for the surgeon. An accurate preoperative diagnosis of pathologies of the septum in the context of the nasal cavity is essential for the success of surgery. Intraoperative visualization through microscope or endoscope is very helpful for the surgeon and for the training of the residents. The modern technique of septoplasty with the phases of approach, mobilization, resection/repositioning and reconstruction/fixation is presented. Furthermore, the extracorporeal septoplasty in extreme deviations of the septum and alternative techniques for use in cases with limited pathologies as well as aspects of septoplasty in children are discussed. As particularly pathologies of the caudal septum are responsible for failures of septal surgery, some special problems of this region such as the vertical fracture of the caudal septum, the lack of caudal septum or anterior convexities of the cartilaginous septum are argued. Finally, advices for the management of intra-and postoperative complications are given.
Gesehen am 15.12.2022